Becoming Editor: Or, Pinocchio finally notices the Strings - Martin Parker (tripleC: Communication, Capitalism & Critique)
This paper uses my experience as an academic journal editor in order to reflect upon the social arrangement that brings academics, universities, states and knowledge capitalist organizations together to produce the contemporary academic journal and access paywalls. After some consideration of the history of publishing, I analyse the market for articles like this one, and considerthe consequences of the ranking and monetization of journals, papers andcitations by different agents. As I do this, I insert various biographical reflections on the relationship between ‘editing’ and being ‘edited’. The overall aim of the paper is to suggest that this set-up actually has some verynegative consequences for taxpayers, academics and students. It encourages the overproduction of academic output because it turns it into a commodity which is traded, whilst simultaneously tending to discourage forms of knowledge production that fail to fit into the boxes which have already been establishedfor them, whether in terms of content or style. I conclude with some thoughts on open access journals, and their limits.